Back Cover: 161Dy Time‐Domain Synchrotron Mössbauer Spectroscopy for Investigating Single‐Molecule Magnets Incorporating Dy Ions (Angew. Chem. Int. Ed. 11/2019). Issue 11 (18th January 2019) - Scherthan, Lena; Schmidt, Sebastian F. M.; Auerbach, Hendrik; Hochdörffer, Tim; Wolny, Juliusz A.; Bi, Wenli; Zhao, Jiyong; Hu, Michael Y.; Toellner, Tom; Alp, E. Ercan; Brown, Dennis E.; Anson, Christopher E.; et al.
Abstract : Single‐molecule magnets can be investigated by means of 161 Dy time‐domain Mössbauer spectroscopy. In their Communication on page 3444 ff., L. Scherthan, A. K. Powell, V. Schünemann, and co‐workers report how the 161 Dy nucleus can be used to probe the magnetic properties of Dy‐containing compounds directly from the viewpoint of the lanthanide ions.